Rationalizing Choice: A Review Essay on Peter Leeson’s WTF?!: An Economic Tour of the Weird - Sethi, Rajiv (Journal of Economic Literature, 2019)
The methodology of economics has been applied with increasing frequency to non-market behavior and interactions. Peter Leeson’s book WTF?!: An Economic Tour of the Weird illustrates both the promise and the perils of this practice. When applied judiciously to environments in which the strategic obfuscation of true motives is widespread, the economic approach can yield valuable insights. But when applied without proper attention to prevailing norms and values, the attempt to rationalize behavior can fall flat and invite ridicule. Economists seeking to understand cultural practices would do well to import insights from other disciplines, and temper their eagerness to export narrow conceptions of rationality. (JEL A12, B41, D01, D10, D23, Z13)